Two-particle Bose-Einstein correlations in pp collisions at √s=13 TeV measured with the ATLAS detector at the LHC - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (The European physical journal. C, Particles and fields, 2022)
This paper presents studies of Bose–Einstein correlations (BEC) in proton–proton collisions at a centre-of-mass energy of 13 TeV, using data from the ATLAS detector at the CERN Large Hadron Collider. Data were collected in a special low-luminosity configuration with a minimum-bias trigger and a high-multiplicity track trigger, accumulating integrated luminosities of 151 μb−1 and 8.4 nb−1, respectively. The BEC are measured for pairs of like-sign charged particles, each with |η|<2.5, for two kinematic ranges: the first with particle pT>100 MeV and the second with particle pT>500 MeV. The BEC parameters, characterizing the source radius and particle correlation strength, are investigated as functions of charged-particle multiplicity (up to 300) and average transverse momentum of the pair (up to 1.5 GeV). The double-differential dependence on charged-particle multiplicity and average transverse momentum of the pair is also studied. The BEC radius is found to be independent of the charged-particle multiplicity for high charged-particle multiplicity (above 100), confirming a previous observation at lower energy. This saturation occurs independent of the transverse momentum of the pair.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer Zu Theenhausen, P.S. Ott, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 15.02.2023